Influence of growing systems and non-fertilizer ameliorants on microclimate and growth of Brazilian spinach - Strayker Ali Muda; Benyamin Lakitan; Andi Wijaya; Susilawati (Pesquisa Agropecuária Tropical, 2023)
Brazilian spinach is a leafy vegetable originating from the tropical region of South America. Despite the similarity in agroclimatic conditions, this nutrient-rich plant has not been widely cultivated in southeast Asia. Therefore, this research aimed to determine the most suitable growing technique (conventional, floating or bottom-wet culture systems) for Brazilian spinach grown in the wet tropical climate. Non-fertilizer ameliorants were applied to improve the physical characteristics of the growing substrate, making it more permeable. The addition of fine sand and/or rice husk biochar to the growing substrate did not increase the growth rate and the leaf yield of Brazilian spinach. The floating and bottom-wet culture systems performed better, when compared to the conventional system commonly practiced by farmers, particularly during the onset of the dry season. The harvest period lasted from 6 to 9 weeks after planting (WAP). The rate of leaf fresh weight to the total shoot weight gradually decreased during the harvest period, along with the percentage of marketable yield. Related to microclimate conditions, the floating and bottom-wet culture exhibited a higher substrate humidity, while the canopy temperature was not significantly affected by the air or substrate temperature. The substrate temperature measured at midday was significantly higher in the conventional system due to a decrease in the substrate water. In conclusion, Brazilian spinach is suitable for cultivation in wet tropical climate zones, with the application of floating or bottom-wet culture systems and harvest between 6 and 9 WAP emerging as the recommended approach.